Advanced Functional Polymers: The Role of Tyrosine-Coumarin Modifications in Optical and Electrical Performance - Beyazay, Beste; Celik, Hilal; Yucel, Yunus; Ozdemir, Mucahit; Caliskan, Eray; Koran, Kenan; Biryan, Fatih (Amer Chemical Soc, 2025)
Advanced functional polymeric materials can possess chemical reactivity, catalytic properties, photosensitivity, electrical conductivity, biological activity, biocompatibility, pharmacological properties, selective separation, and energy conversion of traditional polymers. Because of these properties, the production and characterization of functional polymers has become an essential part of modern industry and advanced technology. Methacrylate polymers are highly versatile materials owing to their exceptional properties including superior optical transparency, excellent light transmission, and robust thermal stability. This study investigates a class of methacrylate polymers coincorporating coumarin and tyrosine units, aiming to explore the synergistic effects of these moieties on the polymers' optoelectronic properties. The polymers were synthesized and characterized, revealing significant alterations in electronic structure due to the incorporation of coumarin-tyrosine hybrids into the methacrylate backbone. Optical properties were assessed via UV-vis and photoluminescence spectroscopy, demonstrating solvent-dependent red shifts and intense emission peaks, indicative of efficient charge transfer between tyrosine and coumarin. The results highlight the potential of these novel methacrylate polymers for applications in optoelectronics and offer new insights into their synthesis, functionalization, and performance. In this study, the diode properties of polymers were observed that the polymers exhibited effective diode behavior with calculated ideality factors (n) of 2.68 and 2.78, and barrier heights (Phi b) of 0.45 and 0.46 eV, respectively, indicating a more significant effective barrier height compared to previously reported studies. This work contributes to the expanding knowledge of tunable and semiconducting polymers, paving the way for future innovations in advanced material science.
Keywords: Capacitance-Voltage; Series Resistance; Methacrylate; Copolymers; Exchange; Delivery; State